Urban morphological analysis framework for conservation planning and management - Mohamed, Syahidah Amni; Harun, Nor Zalina; Abdullah, Alias (Malaysian Institute of Planners, 2018)
A closer look on scientific research and professional practice concerning on the planning and management of historic towns significantly reveals the absence of integrated approaches for urban morphological analysis as a diagnostic tool to interpret the evolutionary process of its physical form. Such circumstances have influenced the transformation of urban fabric which eventually contributed to fragmented urban landscape. This study aims to provide a unifying conceptual framework represented by morphological aspects of city block as spatial units. Through a conceptual comparative approach, the framework draws upon a typomorphological approach that integrates the process typological approach and historico-geographical approach. The findings revealed that there were three main phases in construing the framework. Firstly, the pertinent basis of urban analysis can be delineated at the typological scale of city (citta); representing by building typology at its most basic level. Consequently, to establish the interrelationship between elements of urban form, the most relevant level of resolution is on the taxonomy of sertum (block) and textus (plot series); emphasizing the representation of urban block as spatial unit. In the final phase, the inherited spatial structure of the town is unveiled according to four process of morphological region. The framework developed will ensure a clear urban form which is necessary for technical functioning and visual legibility for conservation of Early Malay town.